2008
DOI: 10.1108/03074800810846010
|View full text |Cite
|
Sign up to set email alerts
|

Citation impact of Open Access journals

Abstract: Purpose -This literature review aims to provide a synthesis of available key information about the citation impact of Open Access journals in LIS and science in general. Citation impact is defined as a surrogate measure of citation counts. Design/methodology/approach -Based on a literature review, this paper discusses the methodology of the data collections for citation counts. The literature review is structured to address the literature about citation impact of Open Access journals. Findings -The literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Much, though not all, of the literature confirms that an OA citation advantage exists to varying degrees, depending on the discipline. Craig, Plume, McVeigh, Pringle, and Amin (2007) and Turk (2008) provided thorough reviews of this literature. As one example, from many, Norris et al (2008) found significant citation advantages in economics (77%), mathematics (71%), ecology (49%), and sociology (103%).…”
Section: Discussionmentioning
confidence: 99%
“…Much, though not all, of the literature confirms that an OA citation advantage exists to varying degrees, depending on the discipline. Craig, Plume, McVeigh, Pringle, and Amin (2007) and Turk (2008) provided thorough reviews of this literature. As one example, from many, Norris et al (2008) found significant citation advantages in economics (77%), mathematics (71%), ecology (49%), and sociology (103%).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that OA use is highly influenced by the website interface of the publishers or their full‐text access policy (Davis & Price, 2006), or that OA use simply depends on whether an article is hung on the webpage of a more prestigious publishing company or on personal or institutional pages, as stressed by Eysenbach (2006). Bessemer (2006) and Turk (2008) disputed the methodology used to compute citations, arguing that a reasonable period of time should elapse to accurately evaluate impact and avoid short‐term, categorical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Turk (2008) has stated that open access journals are not necessarily new publications. Many established journals make only a few recent years of content available online, while the majority of content is accessible only through traditional access paths.…”
Section: Difference In Citing To Open Access Journals Non-open Accesmentioning
confidence: 99%